Transparent ultra-slip coating with intelligent photothermal dynamic anti-fouling function and preparation method thereof
Through layer-by-layer self-assembly and molecular brushing technology, combined with PNIPAM and MXene materials, an intelligent photothermal dynamic anti-fouling coating was prepared, which solved the problems of poor anti-fouling effect of existing coatings under static conditions and easy loss of lubricating fluid, achieving efficient and long-lasting anti-fouling and ultra-slip performance.
Patent Information
- Application Number
- CN202411854361.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing marine anti-fouling ultra-slip coating has poor anti-fouling effect under static conditions, and the lubricating fluid is easily lost in the marine environment, shortening the service life of the coating.
Using layer-by-layer self-assembly and molecular brushing technology, combined with PNIPAM and MXene materials, an intelligent photothermal dynamic anti-fouling coating was prepared. The coating dynamically adjusts surface affinity and temperature changes through photothermal actuation function, and improves superslip properties and antifouling capabilities through PDMS molecular brushes.
It achieves efficient anti-fouling and ultra-slip performance under different environmental conditions, extends the service life of the coating, and improves the static anti-fouling effect.
Smart Images

Figure CN119307146B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of marine antifouling ultra-slip coating materials, and specifically relates to a transparent ultra-slip coating with intelligent photothermal dynamic antifouling function and a preparation method thereof. Background Art
[0002] Marine biofouling, a long-standing problem faced by humans since they began engaging in maritime activities, has had serious negative impacts on human society. For example, fouling organisms attach to the surface of the hull, increasing navigation resistance, exacerbating energy consumption and greenhouse gas production; fouling organisms clog underwater piping systems; secretions released by fouling organisms cause microbial corrosion, shortening the service life of marine equipment; fouling organisms travel across borders and oceans with ships, causing invasion of alien species and threatening marine ecological security, etc.
[0003] At present, applying antifouling coatings on the surface of ships and marine facilities is the most effective measure to deal with the above problems. In the actual engineering application process, in order to achieve a higher antifouling efficiency, the design and development of antifouling coatings mainly revolve around the release process of antifouling agents. The antifouling principle is to gradually release antifouling agents during service, forming a biotoxic environment on its surface to eliminate or disperse fouling organisms. However, with the implementation of environmental protection laws and regulations, the use of biotoxic materials in the marine environment has begun to be restricted. Therefore, in recent years, the design and development of antifouling coatings has gradually focused on the nature of fouling adhesion, and achieved anti-fouling biological adhesion through surface interface means, thereby developing non-toxic fouling-releasing coating materials. The antifouling principle is to weaken the physical interaction between fouling organisms and the coating surface through low surface free energy, thereby reducing the adhesion of fouling organisms on the coating surface.
[0004] Nature has provided researchers with many effective anti-fouling ideas. Among them, the lotus leaf-like superhydrophobic antifouling coating can interfere with the adhesion process of fouling organisms due to its low surface free energy and micro-nanoscale rough structure. However, the coating has limitations such as unstable solid-gas interface and easy damage to the microstructure. In recent years, liquid-infused porous surface coatings inspired by pitcher plants have attracted much attention. This coating uses its unique microstructure to produce capillary action to lock the inert lubricant on the coating surface, thereby giving the coating excellent lubrication properties. However, this super-slip coating faces the following two problems: This coating needs to be flushed with water flow to detach the loosely attached fouling organisms, so it has poor static anti-fouling effect during ship docking or when serving on various marine facilities; in the actual marine environment, it is difficult to ensure the stability of the lubricant by physical capillary action alone, which can easily lead to the rapid loss of the lubricant under the shear force of the water flow, shortening the service life of the coating. Summary of the invention
[0005] In response to the current major technical problem - how to prepare a coating that is transparent, super-slippery, intelligently responsive and easy to prepare, the present invention provides an intelligent super-slip anti-fouling coating based on layer-by-layer self-assembly and molecular brush technology and a preparation method thereof, the purpose of which is to prepare the coating on surfaces of different roughness, different curvature and different chemical composition with a simple process, to give the substrate dynamic super-slip properties and the function of slowing down the adhesion of biological fouling.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function, specifically comprising the following steps:
[0008] Step 1. Preparation of thermosensitive polymer:
[0009] N-isopropylacrylamide (NIPAM) monomer and azobisisobutyronitrile (AIBN) were added to dioxane, and after magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. After the reaction was completed, the reaction solution was diluted, precipitated with cyclohexane, filtered, and washed. The obtained cyclohexane solution was stirred, filtered, and dried to obtain linear PNIPAM powder.
[0010] Step 2. Preparation of photothermal actuated coating:
[0011] The PNIPAM powder obtained in step 1 is added to the MXene aqueous solution, stirred and ultrasonicated to obtain a stable PNIPAM-MXene mixed solution;
[0012] The cleaned substrate is alternately immersed in a polydiallyldimethylammonium chloride (PDDA) solution and a PNIPAM-MXene mixed solution, and the PDDA / PNIPAM-MXene composite coating is deposited on the substrate through the electrostatic attraction of opposite charges.
[0013] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0014] Isopropanol, dimethyldimethoxysilane (DMDMS) and concentrated sulfuric acid are mixed to prepare a PDMS precursor solution, and the PDDA / PNIPAM-MXene composite coating obtained in step 2 is then immersed in the PDMS precursor solution, then taken out and allowed to react, and finally rinsed with isopropanol, toluene, and deionized water and dried in turn to obtain a transparent ultra-slip coating with intelligent photothermal dynamic anti-fouling function.
[0015] in:
[0016] In the step 1, the molar ratio of NIPAM to AIBN is 100:(0.25-1.25), and the molar ratio of NIPAM to dioxane is 2:(1-2) (mol:L).
[0017] In the step 1, the reaction temperature is 30° C. to 60° C., and the reaction time is 6 h to 18 h. After the reaction is completed, the volume of the reaction solution is diluted by 1 to 3 times with dioxane.
[0018] In the step 2, the mass ratio of PNIPAM powder to MXene in the MXene solution is (0.5-6):1; the mass concentration of the MXene solution is 0.1 mg / mL-1 mg / mL.
[0019] In the step 2, the mass concentration of the PDDA solution is 0.1 mg / mL to 1 mg / mL.
[0020] In the step 2, after the PNIPAM powder is added to the MXene aqueous solution, the stirring time is 30 min to 60 min, and the ultrasonic time is 20 min to 60 min.
[0021] In step 2, the substrate cleaning process is as follows: the substrate is ultrasonically cleaned in an ethanol solution for 10 min to 60 min and then dried, and then cleaned with an oxygen plasma cleaner at 200 W to 300 W for 5 min to 10 min.
[0022] In step 2, the cleaned substrate is immersed in the two solutions for 10 min to 30 min, rinsed with deionized water for 1 min to 2 min before immersion in different solutions, and blown dry with nitrogen.
[0023] In the step 3, isopropanol and DMDMS are analytically pure, and the mass fraction of concentrated sulfuric acid is 98%; the mass ratio of isopropanol to DMDMS solution and concentrated sulfuric acid is 100:(5-10):1.
[0024] In the step 3, the immersion time of the composite coating in the PDMS precursor solution is 10 s to 60 s; the temperature of the static reaction is 25° C. to 40° C., the ambient humidity is 30% RH to 50% RH, and the reaction time is 30 min to 60 min.
[0025] A transparent ultra-slip coating with intelligent photothermal dynamic anti-fouling function is prepared by the above preparation method.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention combines a certain proportion of PNIPAM and MXene to give the material the functions of photothermal conversion and photothermal actuation. As the ambient light intensity and temperature change, micro-nanoscale phase changes occur on the surface of the material.
[0028] 2. The present invention adopts a chemical covalent method to graft a layer of PDMS flexible molecular brush on the surface of the coating, which gives the material super-slippery properties, reduces the adhesion between biological fouling and materials, improves the anti-fouling ability of the coating and improves the durability of the material.
[0029] 3. The bionic coating for preventing marine biofouling provided by the present invention has stability, durability, universality and high efficiency, and provides a way for the development of efficient antifouling coatings in marine engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A flow chart of the preparation of a transparent ultra-slip coating with intelligent photothermal dynamic anti-fouling function according to the present invention;
[0031] Figure 2 Scanning electron microscope images of a blank silicon wafer, (PDDA / PNIPAM-MXene)6, and (PDDA / PNIPAM-MXene)6@PDMS composite coating in Example 1 of the present invention; wherein, Figure (a) is a blank silicon wafer, Figure (b) is a (PDDA / PNIPAM-MXene)6 composite coating, and Figure (c) is a (PDDA / PNIPAM-MXene)6@PDMS composite coating;
[0032] Figure 3 Energy dispersion image of (PDDA / PNIPAM-MXene)6 composite coating in Example 1 of the present invention;
[0033] Figure 4 X-ray photoelectron spectrum of the (PDDA / PNIPAM-MXene)6@PDMS composite coating in Example 1 of the present invention;
[0034] Figure 5 In Examples 1-4 of the present invention, (PDDA / PNIPAM-MXene) n Comparison of light transmittance of composite coatings with different numbers of layers;
[0035] Figure 6 Photothermal conversion efficiency diagram of (PDDA / PNIPAM-MXene)6 composite coating in Example 1 of the present invention;
[0036] Figure 7In Example 1 of the present invention, an atomic force microscope image of the (PDDA / PNIPAM-MXene)6 composite coating and a statistical graph of the Young's modulus of the (PDDA / PNIPAM-MXene)6 composite coating and the (PDDA / MXene)6 composite coating at different temperatures;
[0037] Figure 8 In Example 1 of the present invention, the contact angle data of the (PDDA / PNIPAM-MXene)6@PDMS composite coating at different temperatures;
[0038] Fig. 9 In Example 1 of the present invention, the renderings of anti-fluorescein labeled bovine serum albumin (BSA-FITC) of a blank silicon wafer at room temperature and high temperature and of a (PDDA / PNIPAM-MXene)6@PDMS composite coating at room temperature and high temperature are shown; wherein, Figure (a) is a rendering of a blank silicon wafer at room temperature, Figure (b) is a rendering of a blank silicon wafer at high temperature, Figure (c) is a rendering of a (PDDA / PNIPAM-MXene)6@PDMS composite coating at room temperature, and Figure (d) is a rendering of a (PDDA / PNIPAM-MXene)6@PDMS composite coating at high temperature;
[0039] Fig.10 A diagram showing the anti-E. coli effect of the (PDDA / PNIPAM-MXene)6@PDMS composite coating in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0041] Experimental methods without specifying specific conditions are usually carried out under conventional conditions, such as those described in textbooks and experimental guides, or under conditions recommended by manufacturers, which are well known or easily known to ordinary technicians in the field. The following examples are only preferred embodiments of the present invention and do not limit the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
[0042] In an embodiment of the present invention, a thermal response actuator that can dynamically change the interfacial hydrophilicity or surface roughness in response to changes in ambient temperature is added to the coating to solve the problem of poor static anti-fouling ability of the fouling-release coating; a photothermal conversion layer is added to the coating to convert the thermal response actuator into photothermal actuator, thereby reducing the response difficulty of the actuator layer; and a polymer molecular brush with liquid-like properties is chemically covalently grafted on the coating surface to achieve low material surface energy and long-term service life of the material, thereby further improving the static and dynamic anti-fouling effects of the coating.
[0043] The macromolecular chain of poly (N-isopropylacrylamide) (PNIPAM) has both hydrophilic acylamino and hydrophobic isopropyl groups, which makes the aqueous solution of linear PNIPAM exhibit temperature-sensitive properties. When the aqueous solution of PNIPAM is heated to about 33°C, a phase change occurs, from a homogeneous system to a heterogeneous system. Thanks to the thermal responsiveness of PNIPAM and its suitable response temperature, it is used as a thermally responsive actuating component in the embodiments of the present invention.
[0044] MXene is a two-dimensional transition metal carbide, nitride or carbonitride with hydroxyl groups or terminal oxygen on its surface, so it has high chemical activity and a large number of reaction sites, and often serves as the basis for secondary reactions; due to its high electromagnetic wave absorption capacity and local surface plasma effect, MXene has an internal photothermal conversion efficiency of up to 100%, so it is used as the photothermal conversion material in the present invention.
[0045] Based on this, in the embodiment of the present invention, the thermosensitive gel PNIPAM and MXene are mixed to prepare a photothermal brake coating that can dynamically switch the surface hydrophilicity and roughness with the changes in ambient light and temperature. On the basis of the photothermal brake coating, a layer of polydimethyldimethoxysilane (PDMS) molecular brush is covalently grafted using the silane chemical method to give the coating a super-slip effect while avoiding the use of lubricating fluid, further improving the high efficiency and long-term anti-fouling effect of the coating.
[0046] The embodiment of the present invention provides a method for preparing a transparent ultra-slip coating with intelligent photothermal dynamic anti-fouling function. Among them, in the coating, MXene gives the coating a photothermal conversion function, and the content of MXene determines the final photothermal conversion effect of the coating. PNIPAM gives the coating a temperature-sensitive phase change function, and the content of PNIPAM determines the degree of phase change on the coating surface. The combination of PNIPAM and MXene can achieve that even when the ambient temperature changes are not obvious, the change in light intensity can still cause PNIPAM to undergo a phase change, thereby improving the high efficiency of the coating's anti-fouling properties. The PDMS molecular brush not only has low surface energy, but its flexible polymer chain gives it liquid-like properties, which greatly enhances the ultra-slip properties of the coating and greatly slows down the residue of droplets and biological fouling on its surface.
[0047] The isopropanol and DMDMS used in the embodiments of the present invention are of analytical grade, and the mass fraction of concentrated sulfuric acid is 98%.
[0048] Example 1
[0049] A method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function, the method flow chart is as follows Figure 1 As shown, the specific steps include:
[0050] Step 1. Preparation of thermosensitive polymer:
[0051] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0052] Step 2. Preparation of photothermal actuated coating:
[0053] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 1:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0054] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0055] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene six times, a composite coating (PDDA / PNIPAM-MXene)6 was deposited on a silicon wafer substrate.
[0056] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0057] Isopropanol, dimethyldimethoxysilane (DMDMS) and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)6 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, and then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)6@PDMS composite superslip coating.
[0058] Example 2
[0059] A method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function, specifically comprising the following steps:
[0060] Step 1. Preparation of thermosensitive polymer:
[0061] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0062] Step 2. Preparation of photothermal actuated coating:
[0063] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 1:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0064] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0065] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene twice, a composite coating (PDDA / PNIPAM-MXene)2 was deposited on a silicon wafer substrate.
[0066] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0067] Isopropanol, dimethyldimethoxysilane (DMDMS) and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)2 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, and then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)2@PDMS composite superslip coating.
[0068] Example 3
[0069] A method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function, specifically comprising the following steps:
[0070] Step 1. Preparation of thermosensitive polymer:
[0071] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0072] Step 2. Preparation of photothermal actuated coating:
[0073] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 1:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0074] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0075] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene four times, a composite coating (PDDA / PNIPAM-MXene) 4 was deposited on a silicon wafer substrate.
[0076] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0077] Isopropanol, dimethyldimethoxysilane (DMDMS) and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)4 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, and then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)4@PDMS composite superslip coating.
[0078] Example 4
[0079] A method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function, specifically comprising the following steps:
[0080] Step 1. Preparation of thermosensitive polymer:
[0081] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0082] Step 2. Preparation of photothermal actuated coating:
[0083] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 1:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0084] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0085] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene eight times, a composite coating (PDDA / PNIPAM-MXene) was deposited on a silicon wafer substrate8.
[0086] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0087] Isopropanol, dimethyldimethoxysilane (DMDMS) and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)8 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, and then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)8@PDMS composite superslip coating.
[0088] Example 5
[0089] Step 1. Preparation of thermosensitive polymer:
[0090] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0091] Step 2. Preparation of photothermal actuated coating:
[0092] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 2:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0093] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0094] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene six times, a composite coating (PDDA / PNIPAM-MXene)6 was deposited on a silicon wafer substrate.
[0095] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0096] Isopropanol, dimethyldimethoxysilane (DMDMS) solution and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)6 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)6@PDMS composite superslip coating.
[0097] Example 6
[0098] Step 1. Preparation of thermosensitive polymer:
[0099] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0100] Step 2. Preparation of photothermal actuated coating:
[0101] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 0.5:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0102] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0103] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene six times, a composite coating (PDDA / PNIPAM-MXene)6 was deposited on a silicon wafer substrate.
[0104] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0105] Isopropanol, dimethyldimethoxysilane (DMDMS) solution and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)6 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)6@PDMS composite superslip coating.
[0106] Example 7
[0107] Step 1. Preparation of thermosensitive polymer:
[0108] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0109] Step 2. Preparation of photothermal actuated coating:
[0110] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 6:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0111] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0112] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene six times, a composite coating (PDDA / PNIPAM-MXene)6 was deposited on a silicon wafer substrate.
[0113] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0114] Isopropanol, dimethyldimethoxysilane (DMDMS) solution and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)6 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)6@PDMS composite superslip coating.
[0115] Example 8
[0116] Step 1. Preparation of thermosensitive polymer:
[0117] 20 mL of dioxane was added to a three-necked round-bottom flask, and then 40 mmol of NIPAM monomer and 0.4 mmol of AIBN were weighed and added to the three-necked round-bottom flask. After magnetic stirring to form a uniform solution, nitrogen was continuously introduced for anaerobic reaction. The reaction temperature was 60°C and the reaction time was 12 h. After the reaction, the reaction solution was diluted 1 times, precipitated with cyclohexane, filtered and washed three times. The obtained cyclohexane solution was stirred, filtered and dried to obtain linear PNIPAM powder.
[0118] Step 2. Preparation of photothermal actuated coating:
[0119] The PNIPAM powder obtained in step 1 was added to a 0.1 mg / mL MXene aqueous solution, the mass ratio of PNIPAM powder to MXene in the MXene solution was 4:1, and the mixture was stirred for 30 min and ultrasonicated for 30 min to obtain a stable PNIPAM-MXene mixed solution; the silicon wafer was ultrasonically cleaned in an ethanol solution for 30 min and then dried, and then cleaned with an oxygen plasma cleaner at 300 W for 10 min to obtain a cleaned silicon wafer substrate;
[0120] The cleaned silicon wafer substrate was alternately immersed in a PDDA solution with a mass concentration of 1 mg / mL and a PNIPAM-MXene mixed solution for 15 min, rinsed with deionized water for 2 min between each immersion, and blown dry with nitrogen.
[0121] By alternately electrostatically depositing positively charged PDDA and negatively charged PNIPAM-MXene six times, a composite coating (PDDA / PNIPAM-MXene)6 was deposited on a silicon wafer substrate.
[0122] Step 3. Preparation of smart ultra-slip anti-fouling coating:
[0123] Isopropanol, dimethyldimethoxysilane (DMDMS) solution and concentrated sulfuric acid were mixed in a mass ratio of 100:10:1 to prepare a PDMS precursor solution, and the (PDDA / PNIPAM-MXene)6 composite coating obtained in step 2 was immersed in the PDMS precursor solution for 30 s, then taken out and placed in a constant temperature and humidity chamber (37°C, 45%RH) for 45 min. After the reaction was complete, it was washed three times with isopropanol, toluene and deionized water in sequence, and dried to obtain a (PDDA / PNIPAM-MXene)6@PDMS composite superslip coating.
[0124] The coating prepared in Example 1 was subjected to morphological analysis. Figure 2 It shows that (PDDA / PNIPAM-MXene)6 is firmly bonded and evenly distributed on the silicon wafer substrate, and PNIPAM-MXene "particles" of hundreds of nanometers are evenly distributed on the substrate surface. PDMS is evenly grafted on the (PDDA / PNIPAM-MXene)6 composite coating. Figure 3 The EDS spectrum shows that the entire coating is evenly distributed. Figure 7 The atomic force microscopy images showed that the surface roughness of (PDDA / PNIPAM-MXene)6 at room temperature was as low as 46.5±3.9 nm, and the surface of the material was smooth and uniform.
[0125] The coating prepared in Example 1 was analyzed by X-ray photoelectron spectroscopy. Figure 4 In the X-ray photoelectron energy spectrum, the uniform distribution of C, N, and Cl elements shows the uniform deposition of PDDA; the uniform distribution of C, N, and O elements shows the uniform deposition of PNIPAM; and the uniform distribution of C and Ti elements shows the uniform deposition of MXene.
[0126] The mechanical properties of the coating prepared in Example 1 were analyzed. Figure 7The atomic force microscopy images show that the Young's modulus of (PDDA / PNIPAM-MXene)6 is 3.3 MPa at room temperature, and its modulus increases to 7.0 MPa as the temperature increases, indicating that the temperature change causes an obvious phase change of PNIPAM.
[0127] The optical properties of the coatings prepared in Examples 1-4 were analyzed. Figure 5 The transmittance curve shows that as (PDDA / PNIPAM-MXene) n As the number of composite coating layers increases, the transparency of the coating decreases, but the transmittance remains high in the visible light range. At 550 nm, the transmittances of the composite coatings with 2, 4, 6, and 8 layers are 90.5%, 87.5%, 82.1%, and 80.1%, respectively.
[0128] The photothermal conversion performance of the coating prepared in Example 1 was analyzed. Figure 6 The coating was shown to be 2 ), it only takes 54 s to rise from 23°C to 32°C (PNIPAM low critical phase transition temperature), and the equilibrium temperature reaches about 40°C in about five minutes, indicating that the coating has a high photothermal conversion efficiency and can reach the phase transition temperature requirement of the thermally actuated coating through light irradiation.
[0129] The wettability analysis of the coating prepared in Example 1 was performed. Figure 8 The results show that the smart super-slip coating has a higher static water contact angle and a lower contact angle hysteresis, which proves that it has good lubricity. The droplet remains on the surface of the coating at low temperature for 10 seconds, and slides from the top to the bottom of the coating at high temperature in 1 second, which proves that the coating undergoes significant changes in wettability at different temperatures.
[0130] The coating prepared in Example 1 was subjected to protein resistance analysis. Fig. 9 The fluorescence intensity graph shows that as the temperature increases, the adhesion area of BSA-FITC on the blank silicon wafer increases. On the contrary, the adhesion area of BSA-FITC on the (PDDA / PNIPAM-MXene)6@PDMS coating surface decreases significantly. This phenomenon indicates that as the temperature increases, the interface state of the coating surface switches, which significantly affects the adhesion of BSA-FITC.
[0131] The antibacterial performance of the coating prepared in Example 1 was analyzed. Fig.10 The CFU plate method showed that the antibacterial rate of the (PDDA / PNIPAM-MXene)6@PDMS coating was as high as 89.5%. The colony situation in the culture dish clearly showed the excellent antibacterial effect of (PDDA / PNIPAM-MXene)6@PDMS compared with the blank silicon wafer.
Claims
1. A method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function, characterized in that: The specific steps include: Step 1. Preparation of thermosensitive polymer: N-isopropylacrylamide monomer and azobisisobutyronitrile are added to dioxane, and after magnetic stirring to form a uniform solution, nitrogen is introduced to perform an anaerobic reaction. After the reaction is completed, the reaction solution is diluted, precipitated with cyclohexane, filtered, and washed. The obtained cyclohexane solution is stirred, filtered, and dried to obtain a linear PNIPAM powder. The molar ratio of the N-isopropylacrylamide monomer to azobisisobutyronitrile is 100:(0.25-1.25), and the volume ratio of the N-isopropylacrylamide monomer to dioxane is 2:(1-2) (mol:L); the reaction temperature is 30°C-60°C, and the reaction time is 6 h-18 h; after the reaction is completed, the volume of the reaction solution is diluted by 1-3 times with dioxane; Step 2. Preparation of photothermal coating: The PNIPAM powder obtained in step 1 is added to the MXene aqueous solution, stirred and ultrasonicated to obtain a stable PNIPAM-MXene mixed solution; The cleaned substrate is alternately immersed in a polydiallyldimethylammonium chloride solution and a PNIPAM-MXene mixed solution, and the PDDA / PNIPAM-MXene composite coating is deposited on the substrate through the electrostatic attraction of opposite charges. The mass ratio of the PNIPAM powder to the MXene in the MXene solution is (0.5-6):1; the mass concentration of the MXene solution is 0.1 mg / mL-1 mg / mL; the mass concentration of the polydiallyldimethylammonium chloride solution is 0.1 mg / mL-1 mg / mL; Step 3. Preparation of smart ultra-slip anti-fouling coating: Isopropanol, dimethyldimethoxysilane and concentrated sulfuric acid are mixed to prepare a PDMS precursor solution, and the PDDA / PNIPAM-MXene composite coating obtained in step 2 is immersed in the PDMS precursor solution, then taken out and allowed to react, and finally rinsed with isopropanol, toluene, and deionized water in turn, and dried to obtain a transparent ultra-slip coating with intelligent photothermal dynamic anti-fouling function.
2. The method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function according to claim 1, characterized in that: In the step 2, after the PNIPAM powder is added to the MXene aqueous solution, the stirring time is 30 min to 60 min, and the ultrasonic time is 20 min to 60 min.
3. The method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function according to claim 1, characterized in that: In step 2, the substrate cleaning process is as follows: the substrate is ultrasonically cleaned in an ethanol solution for 10 min to 60 min and then dried, and then cleaned with an oxygen plasma cleaner at 200 W to 300 W for 5 min to 10 min.
4. The method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function according to claim 1, characterized in that: In step 2, the cleaned substrate is immersed in the two solutions for 10 min to 30 min. Before immersing in different solutions, it is rinsed with deionized water for 1 min to 2 min and blown dry with nitrogen.
5. The method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function according to claim 1, characterized in that: In step 3, isopropanol and dimethyldimethoxysilane are analytically pure, and the mass fraction of concentrated sulfuric acid is 98%; the mass ratio of isopropanol to dimethyldimethoxysilane solution and concentrated sulfuric acid is 100:(5-10):
1.
6. The method for preparing a transparent super-slip coating with intelligent photothermal dynamic anti-fouling function according to claim 1, characterized in that: In the step 3, the immersion time of the composite coating in the PDMS precursor solution is 10 s to 60 s; the temperature of the static reaction is 25° C. to 40° C., the ambient humidity is 30% RH to 50% RH, and the reaction time is 30 min to 60 min.
7. A transparent super-slip coating with intelligent photothermal dynamic anti-fouling function, characterized in that: The preparation method according to claim 1 is adopted.
Citation Information
Patent Citations
Photo-thermal dual-response intelligent window and preparation method thereof
CN115503307A
Preparation method of hydrogel driver with high driving rate and strong driving force
CN116333345A